THE ROLE OF TEACHER IN ENHANCING STUDENTS’ SPEAKING SKILL AT THE TENTH GRADE OF MAN 2 MODEL MEDAN - Maharani Yasika; Ameera Fadhillah (Adisam Publisher, 2026)
This study aims to analyze the teacher’s role in enhancing students’ speaking skills at the tenth grade of MAN 2 Model Medan. This study used a descriptive qualitative research design. The data were collected through classroom observation, interviews, and documentation involving one English teacher and tenth-grade students. The data were analyzed using Miles and Huberman’s qualitative analysis techniques, including data reduction, data display, and conclusion drawing. The findings showed that the teacher performed several roles in the classroom, namely as a controller, organizer, prompter, facilitator, and assessor. The teacher managed classroom activities, provided instructions, encouraged students to speak, and gave feedback during speaking activities. However, the implementation of these roles was not fully optimal because interactive speaking activities were still limited and students showed low confidence in speaking English. Therefore, more communicative and interactive teaching approaches are needed to improve students’ speaking skills effectively.